Thirty minutes of daily artificial gravity does not mitigate head down tilt induced brain activity changes during cognitive task performance - Tays, Grant D.; McGregor, Heather R.; De Dios, Yiri E.; Mulder, Edwin; Bloomberg, Jacob J.; Mulavara, Ajitkumar P.; Wood, Scott J.; Seidler, Rachael D. (Frontiers in Neurology, 2025)
IntroductionStudies have shown that microgravity results in high dual task costs when crewmembers perform cognitive-motor dual tasking. Head-down tilt bedrest (HDBR) has been widely used as a spaceflight analog environment, recreating some of the sensorimotor and cognitive changes, headward fluid shifts, and unloading of bones and muscles. Here, we examined whether artificial gravity (AG) mitigates changes in cognitive performance and associated brain activity that occur in the HDBR environment.MethodsWe tested one group of participants (n = 16) that received 30 min of daily AG (half received it continuously while the other half experienced it in 5-min bouts), and one group that did not (n = 8 controls) during the course of 60 days HDBR. Participants performed spatial working memory and cognitive-motor dual tasking prior to entering HDBR, during HDBR and post-HDBR.ResultsBrain activation patterns associated with these two tasks changed with HDBR, but there was no difference between the AG and control groups. Compensatory brain-behavioral change-change correlations were observed, where those who increased activation the most had the least decrease in motor tapping accuracy from pre-HDBR to late-HDBR.DiscussionThese results suggest that AG does not reduce the need for compensatory brain responses that occur with HDBR, but longer duration and/or more optimal AG phasing may be required.